Rituximab therapy for Severe and Persistent Lichenoid drug-reaction - El-Reshaid, Kamel; Al-Bader, Shaima (Journal of Drug Delivery and Therapeutics, 2019)
We report on a patient with severe and fixed lichenoid drug-reaction.  She did not respond to 2 months treatment with high-dose corticosteroids.  Hence, Rituximab was given.  One month later, her lesions improved and remained stable for 14 months of follow up.   Keywords: fixed drug reaction, Prednesone, Rituximab.